PENGARUH MOTIVASI DAN PRESTASI BELAJAR TERHADAP MINAT MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PADA SISWA KELAS XII SMA NEGERI 1 RANGSANG - Siti Wahyuni; Almasdi Syahza; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to analyze the effect of motivation and learning achievement on the interest in continuing education to higher education in class XII students of SMA Negeri 1 Rangsang. The subjects of this study were 93 students of class XII students of High School country 1 Rangsang, the sample was taken using the random sampling method. The data used are primary data and secondary data with data collection techniques using a questionnaire and documentation. The data analysis technique used is Multiple Linear Regression Analysis. The results showed that motivation and learning achievement simultaneously had a significant effect on the interest in continuing education to higher education in class XII students of High School country 1 Rangsang. This means that motivation and high learning achievement will trigger the high interest of students to continue to higher education. Conversely, if the motivation and learning achievement are low, it will lead to low student interest in continuing to college.Key Words: Learning Motivation, Learning Behavior, Interest in Continuing Education in Higher Education